Chlorthalidone, not hydrochlorothiazide, is the right diuretic for comparison - Ravi Tejraj Mehta; Anil Pareek; Indranil Purkait (BMC, 2018)
Abstract We have read the study design "Comparison of effects between calcium channel blocker and diuretics in combination with angiotensin II receptor blocker on 24-h central blood pressure and vascular hemodynamic parameters in hypertensive patients: study design for a multicenter, double-blinded, active controlled, phase 4, randomized trial" by Oh GC, et al. with interest. The authors aim to compare the efficacy of amlodipine or hydrochlorothiazide (HCTZ) with an ARB. However, we wish to highlight that chlorthalidone (CTD) is the evidence-based and recommended anti-hypertensive diuretic, and should replace HCTZ in the trial to effectively compare efficacy against the CCB amlodipine.